ANALISIS FAKTOR RENDAHNYA MINAT BELAJAR MATEMATIKA SISWA KELAS V DI SD NEGERI NGENI 06 KABUPATEN BLITAR - Triya Manika Putra; Alif Mudiono; Candra Utama (Jurnal Ilmiah Global Education, 2022)
This study aims to find out what factors influence the low interest of students in mathematics and how the efforts of teachers in fostering students' interest in learning in Mathematics class V at SD Negeri Ngeni 06 Blitar Regency. The type of research used is qualitative research. Activities in this study were carried out by means of observation, interviews and documentation. Based on the research that has been done, it was found that there are several factors that influence the low interest in learning students in mathematics, including the internal factors of students as indicated by the lack of interest in learning about mathematics and they assume that mathematics is an abstract and difficult subject, students' attention still low in mathematics and has an effect on low student achievement in mathematics. The factor of low student interest in learning also comes from external factors. Based on the results of interviews with teachers, it shows that teachers still use conventional methods and do not maximize existing learning media in teaching mathematics so that they are less attractive to students. Besides that, how to educate parents at home also affects students' learning interest when at school. The conclusion in this study is the efforts made by the teacher in fostering student interest in learning, especially in mathematics by using web-based interactive media (google sites) and using a variety of learning methods.